mTORC1 Transcriptional Regulation of Ribosome Subunits, Protein Synthesis, and Molecular Transport in Primary Human Trophoblast Cells - Rosario, Fredrick J.; Powell, Theresa L.; Gupta, Madhulika B.; Cox, Laura; Jansson, Thomas (Frontiers in Cell and Developmental Biology, 2020)
Mechanistic Target of Rapamycin Complex 1 (mTORC1) serves as positive regulator of placental nutrient transport and mitochondrial respiration. The role of mTORC1 signalling in modulating other placental functions is largely unexplored. We used gene array following the silencing of raptor to identify genes regulated by mTORC1 in primary human trophoblast (PHT) cells. Seven hundred and thirty-nine genes were differentially expressed; 487 genes were down-regulated and 252 up-regulated. Bioinformatic analyses demonstrated that inhibition of mTORC1 resulted in decreased expression of genes encoding ribosomal proteins in the 60S and 40S ribosome subunits. Furthermore, down-regulated genes were functionally enriched in genes involved in eIF2, sirtuin and mTOR signaling, mitochondrial function and glutamine, and Zinc transport. Stress response genes were enriched among up-regulated genes following mTORC1 inhibition. The protein expression of ribosomal proteins RPL26 (RPL26) and Ribosomal Protein S10 (RPS10) was decreased and positively correlated to mTORC1 signaling in human placentas collected from pregnancies complicated by intrauterine growth restriction (IUGR). In conclusion, mTORC1 signaling regulates the expression of trophoblast genes involved in ribosome and protein synthesis, mitochondrial function, lipid metabolism, nutrient transport, and angiogenesis, representing novel links between mTOR signaling and multiple placental functions critical for normal fetal growth and development.